Educational Seismology through an Immersive Virtual Reality Game: Design, Development and Pilot Evaluation of User Experience - Vaia Maragkou; Maria Rangoussi; Ioannis Kalogeras; Nikolaos S. Melis (MDPI AG, 2023)
Virtual Reality (VR), especially in its immersive form, is a promising technology employed to support education and training in various fields. VR offers unique opportunities to experience situations and environments that are otherwise inaccessible or risky. Educational Seismology aims to inform and educate the public on earthquakes; to this end, the use of VR is investigated as an attractive solution. VRQuake is an immersive VR application designed and developed for Educational Seismology purposes. VRQuake is structured in five consecutive scenes and is organized as a game. It allows users to interact with virtual objects in real time and apply learned rules and good practices in reaction to an earthquake, thus providing a dynamic learning environment. A pilot evaluation of VRQuake is performed by volunteer university students who play the game and then answer a questionnaire with closed- and open-type questions referring mostly to the user experience. Analysis of the answers has shown positive results regarding usability, clarity and acceptance of the application. Answers are also encouraging as to the educational potential of VRQuake. Furthermore, qualitative analysis of open-type questions has contributed user suggestions and demands that point to interesting new directions for further improvement of user experience and learning outcomes.